2008
DOI: 10.1063/1.2932282
|View full text |Cite
|
Sign up to set email alerts
|

Three-nucleon interactions: A frontier in nuclear structure

Abstract: Abstract. Three-nucleon interactions are a frontier in understanding and predicting the structure of strongly-interacting matter in laboratory nuclei and in the cosmos. We present results and discuss the status of first calculations with microscopic three-nucleon interactions beyond light nuclei. This coherent effort is possible due to advances based on effective field theory and renormalization group methods in nuclear physics.The physics of strong interactions extends over extremes in density, neutron-to-pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…The experimental linear trend from 41 Ca to 47 Ca and 49 Ca to 51 Ca, a signature of the filling of the f 7/2 and p 3/2 orbitals, suggests that the quadrupole moments are dominated by the single-particle character of the ground states. The MBPT predictions exhibit a very good description of the experimental quadrupole moments, in general similar to KB3G and GXPF1A interactions and better for 47 Ca. Note that the theoretical results use the same neutron effective charges en = 0.5e (97).…”
Section: Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…The experimental linear trend from 41 Ca to 47 Ca and 49 Ca to 51 Ca, a signature of the filling of the f 7/2 and p 3/2 orbitals, suggests that the quadrupole moments are dominated by the single-particle character of the ground states. The MBPT predictions exhibit a very good description of the experimental quadrupole moments, in general similar to KB3G and GXPF1A interactions and better for 47 Ca. Note that the theoretical results use the same neutron effective charges en = 0.5e (97).…”
Section: Spectroscopymentioning
confidence: 97%
“…These deficiencies have been traced to the monopole components of the valence-space Hamiltonian, as these parts are amplified with neutron number, and it has been argued that 3N forces are important for the monopole components (46). This is also supported by the cutoff dependence of the monopole components with NN forces only (47). First investigations of neutron-rich oxygen isotopes with 3N forces (42) have shown that 3N forces lead to repulsive interactions between valence neutrons.…”
Section: Location Of the Neutron Driplinementioning
confidence: 99%
“…Flow of V low k (k = 0, k = 0; Λ) compared to the corresponding momentum-independent contact interaction C 0 (Λ) at LO and NLO, where this coupling is determined entirely from RG invariance and fits to the scattering length a s (at LO) plus effective range r e (at NLO)[73].…”
mentioning
confidence: 99%
“…3 H and 4 He radii are approximately cutoff independent with low-momentum NN and 3N interactions[73,133].…”
mentioning
confidence: 99%
“…Three-nucleon interactions are a frontier in the physics of nuclei [35] and including their contributions in ab-initio calculations of neutron-rich and heavier nuclei presents a central challenge. For the helium isotopes, 3N interactions are crucial for binding energies and radii, for the evolution of nuclear structure with isospin, and for spin-orbit effects (see for example Refs.…”
Section: Challenges For Ab-initio Calculations Of Halo Nucleimentioning
confidence: 99%